Data driven agent-based simulation of traffic system - Nathaniel Putra Akuan Rokanta (2012)
Traffic is an important aspect that revolves around our lives as the need to use transportation becomes more and more noticeable. This increasing need for transportation is one of the forces that motivates researcher to study more about traffic in order to get a better understanding about the phenomenon. By understanding the phenomenon, researcher then aims to address the problems involving traffic. One of the tools that researchers used to study this phenomenon is simulation. Many simulation models in the field of traffic are then developed to assist the study of this phenomenon. One of many methods that are used in developing the simulation includes cellular automata. Cellular automaton is a discrete approach to simulation. This method of simulation is starting to develop more and more in its usage to traffic flow. This project attempts to gain insight of a new addition to the traditional traffic flow models by creating a simulator that have the capability to integrate real world observation data into the simulation. To achieve this goal, the report starts with explaining the objective and the background of this project. The scope of work then gives a clearer view of the things done in the project. The report then moves to explain the basic knowledge needed to understand the report. After the basic understanding of the basic knowledge gained, then the report will move further to the implementation of the simulator. The result of the development of the simulator then is presented to the reader. The simulator created in this project is hoped to bring a new insight to the development of traffic flow models even though there are still flaws that could be fixed and enhanced further from the simulator.